ROLE OF FATHERS BASED ON ISLAMIC EDUCATION CONCEPT AND ITS IMPLEMENTATION OF ISLAMIC SENIOR HIGH SCHOOL (MAN) IN JAKARTA - Bunyanul Arifin, Bunyanul (Tawazun: Jurnal Pendidikan Islam, 2018)
The role of fathers on children is very important and decisive. The success or failure of the child is determined by how the attitude and the way a father do to his children. There are several verses in the Qur’an that describe the magnitude of the role of a father. Similarly in the Sunnah and the life history of the Prophet Muhammad who speaks to the attention of the Prophet towards their children. The Friends and salaf generation also proved how their role in educating their children to become scholars. There are a number of theories about the role of fathers of children that developed since the 1980s until the decade of the 20th century. Michael E. Lamb is an important scientist who pioneered the study of Fathering. A number of other theories continue to grow along with the increasing complexity of fatherhood. In this study the author formulate the role of fathers in the perspective of Islamic education into six dimensions. Based on the results obtained from the questionnaires, surveys, and interviews both to the students, the principal and vice-principal, the authors concluded that the role of the father of the child in the perspective of Islamic education is still not achieved significant results even tend to be small and short of expectations.